Subjective Well-being Analysis as a Return on Investment in Education and its Effects from Socio-Economic Factors by Panel Ordered Probit Method - Setiawan, Tomi; Samith, Muhammad Farras; Mughits, Muhammad Hammam (Quantitative Economics and Management Studies, 2025)
This study attempted to deepen the understanding of how social, economic, and demographic factors affect subjective well-being through the Panel ordered probit method from the Indonesian Family Life Survey (IFLS) 4 and 5. Subjective well-being has emerged as an important indicator of quality of life. Subjective well-being is important for individuals because it reflects the level of happiness and life satisfaction that affects various aspects of life. The research method used is quantitative. Data collection and analysis in this study were conducted through econometric modeling. This research utilizes panel data analyzed using the Panel Ordered Probit Method with the help of STATA 17 software. The results showed that higher education levels increased the likelihood of a person feeling “Very Happy”. In addition to education and age, control variables such as employment status, marital status, and residential location also show a significant influence on happiness; individuals who are employed have a 2.59% higher probability of feeling “Very Happy”, while those who are married tend to be happier and less likely to feel “Unhappy” or “Very Unhappy”. Location of residence was also influential, with individuals living in urban areas 0.97% more likely to feel “Very Happy” compared to those living in rural areas. Overall, the results confirm that education, employment status, social relationships through marital status, and neighborhood are important factors in influencing subjective well-being, emphasizing the importance of investing in education and policies that promote work-life balance and social relationships to improve people's well-being.